Comparison of Two Different Serum-free Media for In Vitro Culture of Bovine Embryos - Se-woong Kim; Yeon-Gil Jung; Jong-im Park; Sangho Roh (The Korean Society of Animal Reproduction and Biotechnology, 2014)
The aim of the present study was to compare two different serum-free media, modified synthetic oviduct fluid (mSOF) and modified potassium simplex optimization medium (mKSOM) containing 20% RD (RPMI1640 + DMEM, 1:1 v/v) (RD-mKSOM), for In Vitro culture (IVC) of bovine embryos. After In Vitro maturation and fertilization, the presumptive zygotes were cultured in two different serum-free conditions for 7 days and 9 days to evaluate blastocyst formation and hatching, respectively. Serum supplemented conventional CR2 medium was used as control. After 7 day of culture, there was no significant difference in cleavage and blastocyst formation rates among three groups (mSOF, 59.3 and 30.1%; RD-mKSOM, 65.0 and 41.5%; control, 51.6 and 38.0%, respectively). Hatching rate was significantly higher in control (69.0%) than other experimental groups (mSOF, 22.0%; RD-mKSOM, 39.5%) (P<0.0001 and P<0.001, respectively). Although both serum-free conditions showed lower hatching rates than serum-added control, in serum-free groups, RD-mKSOM showed significantly higher hatching rate than mSOF (P<0.001). In addition, one-step using RD-mKSOM may facilitate IVC procedure than two-step culture system. In conclusion, the results indicate that one-step RD-mKSOM is more suitable defined culture system for IVC of bovine embryos than two-step mSOF.